Ceramic Alteration Analysis on Roman Pottery: Determining Taphonomy and Use - M. Banducci, Laura (Rei Cretariae Romanae Fautorum Acta, 2015)
In this paper, I introduce the concept of ceramic alteration analysis of Roman pottery: an approach to ceramic study that I have undertaken in an attempt to understand the daily use of cooking and serving vessels in Republican Italy. My broader research employs detailed ceramic study to determine cooking and eating practices; the examination of ceramic alteration is an important component of this research. The methods described here were part of a study I carried out between January 2011 and June 2012 on pottery from the towns of Musarna, near Viterbo, and Populonia, on the Tyrrhenian coast near Livorno. This paper explains why and how I have chosen to implement this approach, and presents a few examples of typical results that I have observed. The purpose of this paper is to make some recommendations about the opportunities, concerns, and limitations inherent in the study of ceramic alteration in the hopes that this type of information will continue to be recorded and published by others in future. The broader application of alteration analysis to other datasets from other contexts would mean that the methods of recording could be refined, and the following observations further confirmed.